Hubungan Antara Pola Makan Dengan Kadar Gula Darah Pada Pasien Diabetes Melitus Tipe 2 Di Puskesmas Sunyaragi Kota Cirebon - Hasya Hauna Aulia Mutaqin; Ignatius Hapsoro Wirandoko; Menik Herdiyanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease characterized by elevated blood glucose levels resulting from impaired insulin secretion, insulin resistance, or a combination of both. Dietary management is an important component of glycemic control in patients with T2DM. Dietary patterns include the type, frequency, and amount of food consumed. This study aimed to determine the association between dietary patterns and blood glucose levels among patients with type 2 Diabetes Mellitus at Sunyaragi Community Health Center, Cirebon City. This study employed an analytic observational design with a cross-sectional approach. The study was conducted at Sunyaragi Community Health Center, Cirebon City, from April to June 2026. The study population consisted of 100 registered patients with type 2 Diabetes Mellitus who underwent routine examinations. A total of 80 respondents were selected using consecutive sampling. Dietary patterns were assessed using a Food Frequency Questionnaire (FFQ), while blood glucose levels were measured using a glucometer. Data were analyzed using univariate analysis and the Chi-Square test. Most respondents had poor dietary patterns, consisting of 66 respondents (82.5%), followed by moderate dietary patterns in 9 respondents (11.3%) and good dietary patterns in 5 respondents (6.2%). A total of 56 respondents (70.0%) had abnormal blood glucose levels, while 24 respondents (30.0%) had normal blood glucose levels. Among respondents with poor dietary patterns, 50 (75.8%) had abnormal blood glucose levels. In contrast, 4 respondents (80.0%) with good dietary patterns had normal blood glucose levels. The Chi-Square test demonstrated a significant association between dietary patterns and blood glucose levels (p=0.019). There was a significant association between dietary patterns and blood glucose levels among patients with type 2 Diabetes Mellitus at Sunyaragi Community Health Center, Cirebon City. Improving dietary patterns should be an important component of education and management for patients with type 2 Diabetes Mellitus in primary healthcare settings.